PENGARUH TAX PLANNING DAN BOOK TAX GAP TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH CREATIVE ACCOUNTING PRACTICE - Supartini, Supartini; Permana, Mochammad Fadzry Nikmatuloh (Universitas 17 Agustus 1945 Jakarta, 2019)
This study aims to prove the effect of tax planning dan book tax gap on the value of the company which is moderated by Creative Accounting Practice. Factors to be considered in this study are tax planning, book tax gaps, corporate values dan creative accounting practices that are calculated through earnings management. This analysis is independent tax planning dan book tax gap variables dan the dependent variable is firm value. This study uses secondary data derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study uses a sample of 24 companies listed on the Stock Exchange in the period 2013-2017. The population selection of this study uses nonprobability sampling method with the type of judgment sampling. The analysis method used in this research is multiple linear regression.The results of hypothesis testing show that the variable tax planning dan book tax gap do not affect the value of the company. Keywords: Tax planning, Firm Value, Profit Management, Creative Accounting Practice, Book tax gap